Novel Global Asymptotic Stability and Dissipativity Criteria of BAM Neural Networks With Delays - Liu, Mei; Jiang, Haijun; Hu, Cheng; Lu, Binglong; Li, Zhanfeng (Frontiers in Physics, 2022)
In this article, issues of both stability and dissipativity for a type of bidirectional associative memory (BAM) neural systems with time delays are investigated. By using generalized Halanay inequalities and constructing appropriate Lyapunov functionals, some novelty criteria are obtained for the asymptotic stability for BAM neural systems with time delays. Also, without assuming boundedness and differentiability for activation functions, some new sufficient conditions for proving the dissipativity are established by making use of matrix theory and inner product properties. The received conclusions extend and improve some previously known works on these problems for general BAM neural systems. In the end, numerical simulation examples are made to show the availability of the theoretical conclusions.